USER INTERFACE AND USER EXPERIENCE DESIGN OF A MOBILE APPLICATION FOR HOUSING CLEANING SERVICES IN CAMPUS AREAS WITH DESIGN THINKING - Kencana, Ardian Bima; Widagdo, Pratama Bayu (LPPM Univ. Ibn Khaldun Bogor, 2025)
Students living in shared accommodation often face difficulties in maintaining the cleanliness of their living spaces due to busy academic schedules, limited time, and ineffective coordination. This situation often leads to shared cleaning schedules being neglected, which in turn affects comfort, health, and productivity. This study aims to design the user interface (UI) and user experience (UX) of a mobile cleaning service application on campus using the Design Thinking approach, which consists of the stages of Empathize, Define, Ideate, Prototype, and Testing. The design process resulted in an interactive prototype with five main features, including group service booking and real-time progress monitoring. Usability testing results showed a high task success rate (average >90%), validating the core functionality. However, challenges in navigation efficiency were identified, as indicated by a misclick rate of 47.6%. Despite this, users' overall perception of the user experience remained highly positive (average score >4.5 out of 5). These findings underscore the importance of applying UI/UX principles in designing responsive digital service platforms tailored to user needs.